Pengaruh Metode Latihan Functional Training Terhadap Peningkatan Power Lengan pada Atlet Basket - Putra Dhawi Anargya; Dikdik Zafar Sidik; Masayu Rizka Risjanna (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The main objective of this study was to analyze and determine the effect of the functional training method on increasing arm power in female basketball athletes at SMAN 6 Cimahi. This research aimed to provide a more specific training alternative to improve explosive power which is crucial for basketball technical skills. This study used a quantitative approach with a quasi-experimental design (single-group pretest-posttest design). The research subjects consisted of 15 female basketball athletes selected through purposive sampling. The intervention was carried out for 9 weeks with a frequency of 2 sessions per week, consisting of an anatomical adaptation phase and a progressive load phase. The measurement tool used was the Medicine Ball Throw Test (3 kg). Data analysis was performed using the Shapiro-Wilk normality test and the paired sample t-test. The results of the study showed a significant increase in arm strength after the intervention. The average score increased from 2.3840 meters in the pre-intervention test to 2.7020 meters in the post-intervention test, showing an average increase of 0.318 meters or 13.34%. Statistical analysis using the Paired Samples T-test yielded a significance value (Sig. 2-tailed) of 0.000 (p < 0.05). This study concludes that the functional training method significantly improves arm power in female basketball athletes. This method is effective in optimizing neuromuscular adaptation and the kinetic chain, which directly impacts the explosive power required for shooting and passing in basketball. Keywords: Basketball, Functional Training, Medicine Ball Throw, Arm Power